Young people in residential care talk about peer violence - Christine Barter (Scottish Journal of Residential Child Care)
Residential care for children has aroused much controversy. Several scandals involving the physical and sexual abuse of residents have led to public inquiries and reports (Kent, 1997; Utting, 1997; Waterhouse, 2000). These have almost all concerned abuse by staff. Research, however, has indicated that children and young people are more likely to be at risk from other residents than from adults (Morris and Wheatley, 1994; Farmer and Pollock, 1998; Sinclair and Gibbs, 1998).